Developing Supply Chain Strategy to Overcome the Lack of Production Capacity, Case Study : Sangkuriang Situ Mukti - Nurcahyo, Mochammad; Dhewanto, Wawan (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract— Supply chain is one of the important aspect in a company because it’s relates to business process ranging from earliest chain up to the end of chain which is customer. According to Lu (2011:8), “a supply chain is basically a group of independent organization connected together through the product and service that they separately and/or jointly add value on in order to deliver them to the end consumer “.In the freshwater fishing industry, supply chain management is needed to ensure that the production process runs smoothly and can supply goods according to market needs. But there is often a company engaged in the fishing industry cannot supply the goods in accordance with the existing demand, one inhibiting factor is due to the lack of production capacity which hampers a company to growth. The study will be conducted based on qualitative method in collecting and abstracting data. The research findings show that most of the farmers has the same problem that is they has lack of production capacity so cannot supply the goods in accordance with existing demand. Further research also proves that integration principle is the most understandable variable by farmers among other orientation variable. Keywords—Recruitment; Supply Chain Management, Production Capacity, and Fishing Industry